Pengaruh Tari Kreasi Terhadap Perkembangan Motorik Kasar Anak Usia 5-6 Tahun Di Taman Kanak-Kanak - Novera Dwi Puspita; Hendi Kariyanto (El-Idare, 2024)
This study aims to examine the impact of creative dance on the gross motor development of children aged 5-6 years at TK Aisyiyah Bustanul Athfal Cabang Jarai. Gross motor development is a crucial aspect of child growth, involving the ability to control large body movements such as running, jumping, and dancing. Creative dance, which combines free movements with a certain structure, is considered to provide good stimulation for children's gross motor development. This research employs a quasi-experimental method with a pretest-posttest control group design. The study sample consists of 30 children divided into two groups: an experimental group that participates in the creative dance program and a control group that does not. Data collection was conducted through observation and gross motor tests before and after the intervention. The results show a significant improvement in the gross motor skills of children who participated in the creative dance program compared to the control group. Statistical analysis using the t-test indicates a p-value of less than 0.05, suggesting that the creative dance program has a positive effect on children's gross motor development. Thus, it can be concluded that creative dance is effective in enhancing the gross motor skills of children aged 5-6 years. This study recommends integrating creative dance programs into early childhood education curricula as a way to support optimal physical development in children.